Islamic Hedging Mechanisms for Exchange Rate Risk: A Shariah-Compliant Perspective - Abdurohman, Dede (Islamicate Institute, 2019)
This paper explores the development and application of Islamic hedging mechanisms to mitigate exchange rate risk in accordance with Shariah principles. Conventional derivatives, often embedded with interest and speculation, are not permissible in Islamic finance. This study investigates alternative tools—such as wa’d-based forwards, Islamic currency swaps, and tahawwut instruments—by examining their jurisprudential foundations, operational models, and institutional frameworks. Using qualitative data from verified academic and institutional sources, the study finds that Shariah-compliant hedging tools are both viable and necessary for effective risk management. However, their broader adoption is hindered by legal diversity, documentation challenges, and regulatory inconsistencies. Opportunities for standardization, technology integration, and educational outreach are identified as pathways for improvement. This research contributes to the discourse by offering a cohesive framework for understanding Islamic hedging and providing actionable insights for regulators, scholars, and practitioners seeking ethical financial risk management solutions.